Conversational Modifications and Feedback in NS-NS and NS-NNS Children's Interactions - Dolan Geraghty, Kathleen (My University, 2007)
This study investigates task and interlocutor effects on feedback in children's interaction. Children were assigned to NS-NS (n=6 pairs) and NS-NNS (n=7 pairs) pairs and engaged in two tasks with their partner: (a) an information gap task and (b) a conversation task. Interactions were recorded and transcribed, and utterances coded for rates of non-target productions and feedback. Non-target productions were further coded by type and whether the utterance triggered feedback from their partner. The results show that children use conversational feedback but use slightly different proportions of each type as compared to adults. Significant main effects of were found for group (experimental vs. control) and speaker type (NS or NNS) on the amount of feedback used in each task, showing that non-native speakers and the experimental group (NS-NNS pairs) received significantly more feedback than NSs. Additionally, the type of feedback triggered by specific errors is discussed.
Keywords: English language; linguistics; conversational modification